Voltage regulation of a stand-alone self-excited induction generator using STATCON with one cycle control technique for wind energy conversion system. Issue 5 (4th July 2017) - Elango, T.; Senthil Kumar, A.
ABSTRACT: This paper presents the simple voltage regulation scheme using a three-phase static VAr compensator (STATCON) for a stand-alone self-excited induction generator (SEIG) that uses variable-speed wind generation system. Most of the loads are inductive and need an equal amount of leading VArs, which is generated by the STATCON and injected at point of common coupling instantaneously. The one cycle control technique is considered and modified to implement for VAr compensation of SEIG voltage regulation. To emphasis the controller characteristics, a STATCON is designed for a 3-Ø, 0.75 kW, 415 V, 1.8 A Induction Machine and tested in simulation using MATLAB/SIMULINK software.